Economic policy and economic development in English-speaking Africa - Onyiriuba, Leonard O. (Lagos : Malthouse Press, 2000)
The book provides an understanding and appreciation of the basic concepts and problems of economic growth and development.
Includes bibliographical references and index.
rua 24/12/13
Loans
Keywords: Africa -- Economic policy; Africa -- Economic conditions